Keeping it real with Bruce Springsteen: How a celebrity brand survives via narrative, authenticity and transparency. Issue 3 (10th June 2019) - McGinnis, Lee Phillip; Glibkowski, Brian C.
Abstract : Purpose: Unlike artists using sartorial flair and flamboyant identities to shock and engage audiences, Bruce Springsteen is relatable, stable, consistent and authentic. Based on qualitative interviews of Springsteen fans of various levels, it is suggested that brands can sustain success through such tactics as existential authenticity, transparency and charity. His fans co-opt his music and co-create their own stories, which are enabled through Springsteen's use of universal themes and vivid details. In terms of a branding paradigm, he adapts to the post-postmodern era, where brands allow individuals to define their own meaning. Design/methodology/approach: The authors used a qualitative method in generating themes and relationships on the enduring success of Bruce Springsteen's brand. They interviewed 19 informants of various levels of fan support and various backgrounds and areas. They used grounded theory methodology, including open coding, triangulation and member checks, to develop themes and findings. Findings: In general, it was found that narrative structure and cause-and-effect stories are at the heart of his enduring success. While his individual songs, stage performances and charitable works cover a variety of topics and interests, combined they map to the same universal story structure, thus giving his fans solid understanding of his brand. His underdog appeal and story of redemption are maintained through such tactics as vivid songwriting, activism and charitable acts despite his international success and fame. Research limitations/implications: Theoretically, the authors add to the literature on celebrity branding, narratology and authenticity. Specifically, the authors build upon the notion of existential authenticity, connecting a brand to its various stakeholders beyond customers in a way that is holistically authentic. We also suggest that to sustain a brand for the long haul, it is necessary to be transparent and available to your community members. The story of your brand needs to resonate and be meaningful to the audience in a way that is believable, and more importantly true to the artist and product. Practical implications: The authors show how narrative structure and universal story themes create ways in which fans can identify. By not straying too far away from the inherent brand meaning, brands can achieve long-term success. Tactically, all ways to manage the brand must link to the main story, but authenticity and maintaining a macromarketing perspective are the keys to making the story believable and enduring. In Springsteen's case, according to our interviews, his music and the message of his well-scripted songs have always mapped well with his real-life persona, making a distinction between his staged persona and actual self visibly difficult to distinguish. Social implications: Part of Bruce Springsteen's enduring success and strong brand are built on his charitable works and activism. Brands that have this aspect will endure as well if motives are transparent, benign and believable. Springsteen has succeeded in this aspect because his charitable works often go unnoticed or unreported, which his fans respect when they discover these acts. Originality/value: Theoretically, the authors also add to the question (i.e. WH-question) literature in terms of connectedness and felt meaning. Springsteen's music connects specific discourse to universal stories/themes via his vivid songwriting, live performances, charitable acts and multiple other tactics. The data suggest that Springsteen's experiences are so vivid and thoughtful that little is needed for the audience to obtain aesthetic or felt meaning of his universal story themes. He allows direct access to the stories without internal interpretation, which then allows for instant penetration of felt meaning.